1989
DOI: 10.1161/01.cir.80.6.1536
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic effects of dipyridamole on atrioventricular nodal conduction and supraventricular tachycardia. Role of endogenous adenosine.

Abstract: Exogenous adenosine has been shown to have potent electrophysiologic effects and antiarrhythmic properties within the atrioventricular (AV) node. Endogenous adenosine, a nucleoside with an increased release signaled by ischemia and hypoxia, is not believed to exert significant effects during homeostatic conditions. Recent experimental evidence suggests, however, that under normoxic conditions, the amount of adenosine released may be sufficient to mediate some of its physiologic effects. This study was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…The mechanism of terminating the arrhythmias by either adenosine or ATP is the induction of transient complete AV nodal conduction block. Dipyridamole, which inhibits the uptake of adenosine and thereby increasing its extracellular levels, was found to reduce the amount of adenosine required for the termination of PSVT involving the AV node [667]. In contrast, it has been suggested that caffeine (a non-selective adenosine receptor antagonist) ingestion reduces adenosine efficacy in the treatment of PSVT [668], although, the methodology of the latter study was subsequently criticised [669].…”
Section: Arrhythmiasmentioning
confidence: 99%
“…The mechanism of terminating the arrhythmias by either adenosine or ATP is the induction of transient complete AV nodal conduction block. Dipyridamole, which inhibits the uptake of adenosine and thereby increasing its extracellular levels, was found to reduce the amount of adenosine required for the termination of PSVT involving the AV node [667]. In contrast, it has been suggested that caffeine (a non-selective adenosine receptor antagonist) ingestion reduces adenosine efficacy in the treatment of PSVT [668], although, the methodology of the latter study was subsequently criticised [669].…”
Section: Arrhythmiasmentioning
confidence: 99%
“…Consistent with experimental findings, adenosine shortens action potential duration and refractoriness.62 These effects may precipitate atrial flutter or fibrillation and is the mechanism by which nucleoside transport blockers like dipyridamole induce atrial flutter that is reversed by aminophylline. 63 AV node. Adenosine slows conduction within the AV node (negative dromotropy), which can result in transient AV block.54,64 Intracardiac recordings demonstrate that heart block is preceded by prolongation of the A-H interval, effects that are unaltered by atropine.…”
Section: Cardiac Electrophysiologymentioning
confidence: 99%
“…The adenosine dose should be reduced to one fourth of the usual dose since dipyridamole potentiates the effects and half-life of adenosine. 63 Patients who are taking competitive antagonists such as theophylline or caffeine may require larger than usual doses of adenosine, although doses as high as 19 mg have been ineffective in patients on theophylline. 70 In heart transplant patients who develop PSVT, the adenosine dose should be reduced to one third to one fifth of the usual dose due to denervation-induced supersensitivity to the drug.…”
Section: Diagnostic Usesmentioning
confidence: 99%
“…In addition, adenosine also prolongs intra-atrial conduction times (Bubinski et al 1989). These effects are thought to be important in the occasional cases of induction by adenosine of atrial flutter (DiMarco et al 1985;Lerman et al 1989). It is likely, therefore, that the induction of atrial fibrillation in this patient by dipyridamole was by a similar mechanism, particularly as no reversible myocardial ischaemia could be demonstrated by thallium tomography.…”
Section: Electrophysiological Effects Of Dipyridamole On the Atriummentioning
confidence: 70%